Zimbabwe tourism destination brand positioning and identity through media: A tourist's perspective - Chigora, Farai; Ndlovu, Joram; Zvavahera, Promise (Goodwood Publishing, 2021)
Purpose: This study aimed to understand how media can be used to select Zimbabwe tourism destination brands against other brands by tourists. Furthermore, it examines the role of the media in improving Zimbabwe’s tourism brand identity. Factors for positioning the Zimbabwe tourism brand were also established. Research Methodology: A quantitative to qualitative sequential mixed method was used to obtain research data. The respondents and participants in the study were tourism operators, media organizations, and tourists (n=452). Results: The study's findings revealed that tourism and media organizations in Zimbabwe fail to understand the best ways to use media to attract tourists. There was a significant disagreement in the views of tourists and organizations, especially when choosing a tourism destination brand using media. Even on improving Zimbabwe tourism destination brand identity and positioning, both parties agreed that media could help improve brand identity. Conclusions: This study highlights that Zimbabwe’s tourism and media organizations struggle to use media effectively for brand promotion. Tourists rely more on word-of-mouth than on media, finding branding symbols and slogans unappealing. However, both parties agree that positive media publicity can improve a destination’s brand identity. Limitations: Obtaining the opinions and views of tourists is difficult considering the divergence in their perceptions. A mixed-methods approach could help improve objectivity. Contributions: The study, therefore, recommends an intensive tourism media audit, considering media as a strategic brand identity tool, and a nationwide survey to determine brand positioning elements specifically for Zimbabwean tourism destinations.